Adecolonialtheoretical-policyanalysisonthefashionconceptanditsuses (ModaPalavra e-periódico, 2020)
Fromapostcolonial/decolonialperspective,thepurposeofthearticleistoquestionthewesternconceptoffashionanditspossibleuses.Weunderstandthattheconceptoffashioncanbeusedasanotionwithinthecolonialideologicalapparatusthatseekstodisallowtherelationshipofnon-westernsocietieswithtimebystatingthatthelatterhasnofashionbecauselittlechangetheirclothing,orasthecolonizerpreferstocallit,yourcostume.Thistypeofbinary,inthecaseof“fashionXcostume”,engenders,asQuijano(2005)pointsout,non-WesternsocietiesandprovidestheWestwiththeideologicalstatusofthemovement,itsabilitytochange,renewitselfand,whynot,evolve(inanevolutionarysense).AsSaid(2007)pointsout,thecolonizer,inhisplaceofauthority,understandsthatitisuptohimto“read”thecolonizedandtotranslatehisculturetohimself
Keywords: fashion; decolonial; capitalism